2014
DOI: 10.3389/fnagi.2014.00146
|View full text |Cite
|
Sign up to set email alerts
|

Differential behavioral and physiological effects of anodal transcranial direct current stimulation in healthy adults of younger and older age

Abstract: Changes in γ-aminobutyric acid (GABA) mediated synaptic transmission have been associated with age-related motor and cognitive functional decline. Since anodal transcranial direct current stimulation (atDCS) has been suggested to target cortical GABAergic inhibitory interneurons, its potential for the treatment of deficient inhibitory activity and functional decline is being increasingly discussed. Therefore, after-effects of a single session of atDCS on resting-state and event-related short-interval intracort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 125 publications
0
44
1
Order By: Relevance
“…Furthermore, to assess short-intracortical inhibition (SICI), we used an interstimulus interval of 2 ms between subthreshold CS and suprathreshold test stimulus for the paired pulse paradigm79. We set our subthreshold CS set at 80% of rMT and suprathreshold TS intensity set to elicit ~1 mV8081. Similar to CBI, we established SICI as a ratio of 10 CS + TS over 10 TS MEPs.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, to assess short-intracortical inhibition (SICI), we used an interstimulus interval of 2 ms between subthreshold CS and suprathreshold test stimulus for the paired pulse paradigm79. We set our subthreshold CS set at 80% of rMT and suprathreshold TS intensity set to elicit ~1 mV8081. Similar to CBI, we established SICI as a ratio of 10 CS + TS over 10 TS MEPs.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in the current study, neither SICI nor ICF showed any modulations in the course of the assessment. Although a number of studies have reported reduced SICI (i.e., released inhibition) following tDCS with the anode placed over M1 (Amadi et al 2015, Cengiz et al 2013, Christova et al 2015, Heise et al 2014, other studies report no change in SICI and ICF following tDCS with the anode placed over M1 (Siebner et al 2004) or increased SICI and reduced ICF (Batsikadze et al 2013). These apparent discrepancies may originate from the fact that both tDCS (duration, current intensity, electrode size) and TMS parameters (inter-stimulus interval, intensities of conditioning pulse) vary somewhat across the studies.…”
Section: Neurophysiological Effects Of Tdcs With the Cathode Placed Omentioning
confidence: 99%
“…The 25 qualified studies were submitted to our meta-analysis. One author (NK) independently coded the 25 studies and extracted data (Berryhill and Jones, 2012;Boggio et al, 2010;Fertonani et al, 2014;Floel et al, 2012;Goodwill et al, 2015;Goodwill et al, 2013;Hardwick and Celnik, 2014;Harty et al, 2014;Heise et al, 2014;Hoff et al, 2015;Holland et al, 2011;Hummel et al, 2010;Jones et al, 2015;Lindenberg et al, 2013;Manenti et al, 2013;Meinzer et al, 2013;Meinzer et al, 2014;Panouilleres et al, 2015;11 Parikh and Cole, 2014;Park et al, 2014;Ross et al, 2011;Sandrini et al, 2014;Seo et al, 2011;Zhou et al, 2015;Zimerman et al, 2013). Two authors (JS & JC) confirmed data extractions, and all authors were involved in interpreting the meta-analytic results.…”
Section: Study Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Interestingly, a reduced capacity to modulate GABA mediated inhibitory processes in older adults (Levin et al, 2014) has been associated with age-related decline in cognitive and motor function (Gleichmann et al, 2011). This raises the possibility of using tDCS to target deficient inhibitory activity in older individuals (Heise et al, 2014).…”
mentioning
confidence: 99%